Antagonism of Protease Activated Receptor-2 by GB88 Reduces Inflammation Triggered by Protease Allergen Tyr-p3 - Wang, Yun-Ju; Yu, Sheng-Jie; Tsai, Jaw-Ji; Yu, Ching-Hsiang; Liao, En-Chih (Frontiers in Immunology, 2021)
Occurrence of allergic diseases induced by aeroallergens has increased in the past decades. Mites remain the important causal agent of allergic diseases. Storage mites-Tyrophagus putrescentiae are found in stored products or domestic environments. Major allergen Tyr-p3 plays a significant role in triggering IgE-mediated hypersensitivity. Its effects on pulmonary inflammation, internalization,and activation in human epithelium remain elusive. Protease-activated receptors(PARs) are activated upon cleavage by proteases. Epithelial cells were used to examine PAR activation by Tyr-p3 and therapeutic potential of PAR-2 antagonist(GB88) in allergic responses. Enzymatic properties and allergen localization of Tyr-p3 were performed. Release of inflammatory mediators, phosphorylation of mitogen-activated protein kinase(MAPK), and cell junction disruptions were evaluated. Enzymatic properties determined by substrate digestion and protease inhibitors indicated that Tyr-p3 processes a trypsin-like serine protease activity. PAR-2 mRNA levels were significantly increased by nTyr-p3 but inhibited by protease inhibitors or GB88. Protease allergen of nTyr-p3 significantly increased the levels of pro-inflammatory cytokines (IL-6 and TNF-α),chemokine(IL-8),and IL-1β in epithelial cells. nTyr-p3 markedly increased phosphorylation of extracellular signal-regulated kinase(ERK)1/2 and MAP kinase. When cells were pretreated with GB88 then added nTyr-p3,the phosphorylated ERK1/2 did not inhibit by GB88. GB88 increased ERK1/2 phosphorylation in epithelium cells. GB88 is able to block PAR-2-mediated calcium signaling which inhibits the nTyr-p3-induced Ca2+ release. Among the pharmacologic inhibitors, the most effective inhibitor of the nTyr-p3 in the induction of IL-8 or IL-1β levels was GB88 followed by SBTI,MAPK/ERK,ERK,and p38 inhibitors. Levels of inflammatory mediators(GM-CSF,VEGF,COX-2,TSLP,and IL-33) were reduced by treatment of GB88. GB88 treatment down-regulated the nTyr-p3-induced PAR-2 expression in allergic patients. Tight junction and adherens junction were disrupted by nTyr-p3 exposure; this effect was avoided by GB88. Immunostaining with frozen sections of mite body showed Tyr-p3 presence throughout the intestinal digestive system,especially in the hindgut around the excretion site. In conclusion, our findings suggest that Tyr-p3 from domestic mites leads to disruption of the airway epithelial barrier after inhalation. Proteolytic activity of Tyr-p3 causes the PAR-2 mRNA expression, thus leading to the release of numerous inflammatory mediators. Antagonism of PAR2 activity suggests GB88 as the therapeutic potential for anti-inflammation medicine, especially in allergy development triggered by protease allergens.